Vaginal Delivery and Maternal Knowledge on Correct Breastfeeding Initiation Time as Predictors of Early Breastfeeding Initiation: Lesson from a Community-Based Cross-Sectional Study. (21st January 2014) - Musa Seid, Abdulbasit
Abstract : Background . Early initiation of breastfeeding is a recommended practice by the World Health Organization (WHO), but in Ethiopia only 52% of the mothers practiced early initiation of breastfeeding. Hence, this study aimed to assess prevalence of early initiation of breastfeeding and the associated factors among mothers in Bahir Dar City, northwest Ethiopia. Methods . A community-based cross-sectional study was conducted among mothers who delivered 12 months before the study began in Bahir Dar City, northwest Ethiopia. A cluster sampling technique was used to select a sample of 819 participants. Bivariate and multivariate analyses were performed. Results . In this study, the prevalence of early initiation was found to be 87.0%. On multivariate logistic regression, delivering vaginally (AOR = 7.37, 95% CI = 4.24, 13.82) and being knowledgeable on correct initiation time (AOR = 6.08, 95% CI = 3.71, 9.95) were found to be independent predictors of early initiation. Conclusions . Prevalence of early initiation of breastfeeding in Bahir Dar city is relatively good but still lower than the national plan. Delivering vaginally and being knowledgeable on correct initiation time were significantly associated with early initiation. Increasing maternal knowledge on correct initiation and providing adequate pain relief and early assistance for mothers who gave birth by C/S were recommended.